Effects of filler volume of nanosisal in compressive strength of composite resin - Dwi Aji Nugroho; W. Widjijono; N. Nuryono; Widya Asmara; Wijayanti Dwi Aastuti; Dana Ardianata (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: One of the composite resin composition is inorganic filler. The production of inorganic filler materials was highly dependent on non-degradable, and nonrenewable fossil fuels. Therefore, natural fibers can be used as substitute for inorganic fillers. One that can be developed is sisal. Purpose: This study aimed to determine the effects of nanosisal filler volume on compressive strength of composite resin. Methods: In this study, composite resins with nano-sized sisal as filler were manufactured and labeled as nanosisal composites. This research processed sisal fibers into nano size and mixed them with Bis-GMA, UDMA, TEGDMA, Champhorquinone (Sigma Aldrich). Nanofiller composite (Z350 XT, 3M, ESPE) was utilized as a control. The 20 samples utilized were divided into 4 groups (each group containing five samples): Group A contained nanosisal composite of 60% filler volume, group B, nanosisal composite of 65% filler volume, group C, nanosisal composite of 70% filler volume and group D, nanofiller composite (Z350 XT, 3M, ESPE). Samples were 2 mm in diameter and 6 mm in height. The sample was tested for compressive strength using a universal testing machine (UTM). Data was analyzed by means of a Kruskal Wallis procedure. Results: The mean of the compressive strength of the nanosisal composite 60% was 16.80 MPa; the nanosisal composite 65% was 10.80 MPa, the nanosisal composite 70% was 7.20 MPa and the nanofiller composite was 7.40 MPa. There was a significant difference in data analysis (p = 0.033; p < 0.05). Conclusion: In this study, the filler volume of nanosisal influenced the compressive strength of a composite resin and the nanosisal filler volume was recomended at 60%.